TREATMENT OF GINGIVAL RECESSION WITH GINGIVAL GRAFT AND PLATELET RICH PLASMA: A CASE REPORT - , Poemomo Agoes Wibisono ([Yogyakarta] : Fak.Kedokteran Gigi Universitas Gadjah Mada, 2012)
Background: Mucogingival surgery was defined as a periodontal surgical procedure designed to correct defects in morphology, position or amount of gingiva surrounding the tooth. Gingival recession was considered to cause tooth sensitivity and may cause esthetic compliance. A wide variety of periodontal plastic surgery have been reported to correct this problem. Purpose: This case report was aimed to demonstrate a clinical success of CT graft and FGG in combination with PRP. Case report 1: 3I-years old female came to treat her receded gums as it sometimes cause sensitivity. After thorough examination we found that it was a class I-Miller gingival recession. There was a lack of keratinized gingiva. Patient wanted to cover the denuded roots without any fillings. A FGG was chosen to be the appropriate therapy. The recipient area was prepared and the donor area on the palate was sliced. PRP was prepared and applied on the recipient bed. After healing, it showed a better root coverage and wide keratinized gingiva with slight color difference. Case Report 2: I8-years old female came to treat her receded gums on the #44. Examination reveal this case as a Class I Miller gingival recession. There was a lack of keratinized gingiva. CT graft was chosen to treat this case. Discussion: These two methods, FGG and CT graft seems to have a predictable result. FGG seems to be easier to take the graft compared to the CT graft. CT graft procedures are technically sensitive. Even, it was more difficult to take, the CT graft offers a blended gingival color, better than the FGG procedure. The use of PRP may enhance the healing properties of this graft. Conclusion: FGG and CT-graft seem to be a predictable procedure to restore gingival recession.